AMINO ACID COMPOSITION OF SOME SKELETAL ELEMENTS OF THE CARP CIRRHINA MRIGALA (HAM.) - Saraswat, R C; Ram, Newton (Indian Journal of Fisheries, 2011)
Results of a study of total nitrogen and amino acid composition of scales and fins of the fish Cirrhina mrigala (Ham.) are reported. Scales contain 1S amino acids of keratin group, glutamic acid, alanine, histidine, lysine and cysteine being absent. Fins contain 1S amino acids of collagen group, threonine, cystine, cysteine, phenyl alanine and hydroxy ly.-ine being absent. Tyrosine content ofscalesandarginine content of fins were maximum. Amounts of amino acids and amino acid nitrogen are greater in fins than in scales, though the total nitrogen content of scales is greater.